Monitoring the Risk of Type-2 Circulating Vaccine-Derived Poliovirus Emergence During Roll-Out of Type-2 Novel Oral Polio Vaccine - Corey M. Peak; Hil Lyons; Arend Voorman; Elizabeth J. Gray; Laura V. Cooper; Isobel M. Blake; Kaija M. Hawes; Ananda S. Bandyopadhyay (Vaccines)
Background/Objectives: Although wild poliovirus type 2 has been eradicated, the prolonged transmission of the live- attenuated virus contained in the type-2 oral polio vaccine (OPV2) in under-immunized populations has led to the emergence of circulating vaccine-derived poliovirus type 2 (cVDPV2). The novel OPV2 (nOPV2) was designed to be more genetically stable and reduce the chance of cVDPV2 emergence while retaining comparable immunogenicity to the Sabin monovalent OPV2 (mOPV2). This study aimed to estimate the relative reduction in the emergence risk due to the use of nOPV2 instead of mOPV2. Methods: Data on OPV2 vaccination campaigns from May 2016 to 1 August 2024 were analyzed to estimate type-2 OPV-induced immunity in children under 5 years of age. Poliovirus surveillance data were used to estimate seeding dates and classify cVDPV2 emergences as mOPV2- or nOPV2-derived. The expected number of emergences if mOPV2 was used instead of nOPV2 was estimated, accounting for the timing and volume of nOPV2 doses, the known risk factors for emergence from mOPV2, and censoring due to the incomplete observation period for more recent nOPV2 doses. Results: As of 1 August 2024, over 98% of the approximately 1.19 billion nOPV2 doses administered globally were in Africa. We estimate that approximately 76 (95% confidence interval 69–85) index isolates of cVDPV2 emergences would be expected to be detected by 1 August 2024 if mOPV2 had been used instead of nOPV2 in Africa. The 18 observed nOPV2-derived emergences represent a 76% (74–79%) lower risk of emergence by nOPV2 than mOPV2 in Africa. The crude global analysis produced similar results. Key limitations include the incomplete understanding of the drivers of heterogeneity in emergence risk across geographies and variance in the per-dose risk of emergence may be incompletely captured using known risk factors. Conclusions: These results are consistent with the accumulating clinical and field evidence showing the enhanced genetic stability of nOPV2 relative to mOPV2, and this approach has been implemented in near-real time to contextualize new findings during the roll-out of this new vaccine. While nOPV2 has resulted in new emergences of cVDPV2, the number of cVDPV2 emergences is estimated to be approximately four-fold lower than if mOPV2 had been used instead.